When y is inversely proportional to the square of x, it satisfies the equation

y = k/x^2

for some constant k. Using the given information, we can find k to be

k = y*x^2 = (1/9)*4^2 = 16/9

Then when x=12, we have

y = (16/9)/12^2 = 16/(9*16*9) = 1/81

When y is inversely proportional to the square of x, it satisfies the equation

y = k/x^2

for some constant k. Using the given information, we can find k to be

k = y*x^2 = (1/9)*4^2 = 16/9

Then when x=12, we have

y = (16/9)/12^2 = 16/(9*16*9) = 1/81

When y is inversely proportional to the square of x, it satisfies the equation

y = k/x^2

for some constant k. Using the given information, we can find k to be

k = y*x^2 = (1/9)*4^2 = 16/9

Then when x=12, we have

y = (16/9)/12^2 = 16/(9*16*9) = 1/81

Y = 1/X^{2}You can see this is 1/3 as the answer. Equality.

1/9 over 4 = Y/12

4Y = 1/9 * 12

4Y = 4/3

Y = 1/3

======

1/9 over 4 = Y/12

4Y = 1/9 * 12

4Y = 4/3

Y = 1/3

======

Didn't find the answer you were looking for?